Anarchy and the Art of Listening : The Politics and Pragmatics of Reception in Papua New Guinea - Slotta, James, 1979- (Book collections on Project MUSE., 2023)
"A study of the role of listening in the political life of anarchic communities in Papua New Guinea's Yopno valley"--